Examining morality and corruption in South African post apartheid contemporary drama : a case of three dramas - Thela, Bongani Clearance (My University, 2018)
The purpose of this study was to examine South Africa’s Post-Apartheid contemporary drama. Three dramas were used in order to examine three primary themes namely morality, corruption and class - the selected plays were John Kani’s Nothing but the Truth, Zakes Mda’s Our Lady of Benoni and Mike van Graan’s Some Mother’s Sons. The ideology carried out in this study was that there is a possible reinvention of Apartheid issues in Post-Apartheid South African drama, exchanging themes of protest and race for morality and corruption, while reflecting real events in the works of playwrights. Also, the study aimed at finding out whether there are connections between class issues and morality as presented in the selected plays. The study found that there is indeed a reinvention of Apartheid issues in Post-Apartheid South Africa, and that there are connections between class issues and morality, including corruption. Lastly, the study concluded that the current South Africa requires a serious intervention regarding moral regeneration as reflected in the selected plays.
Thesis (M.A. (English Studies)) --University of Limpopo, 2018
Keywords: Morality; Corruption; Plutocracy; Post-Apartheid; Virginity; South African literature (English) -- History and criticism; English drama -- History and criticism; Politics and literature -- South Africa; Apartheid in literature